ANALYSIS OF RESPONSIBILITY ACCOUNTING PRACTICES AS A PERFORMANCE ASSESSMENT TOOL (Study at PT. SUR Kaltim) - Nurul Permatasari, Rika; Masiyah, Masiyah Kholmi; Juanda, Ahmad Juanda (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2025)
Every company founded by one or a group of people basically aims to increase customer satisfaction. If customers are satisfied, then profit can be obtained automatically. To achieve this goal, management must make decisions quickly and accurately. This situation requires top management to delegate authority accompanied by a system of control, supervision and performance assessment of managers below. This can be achieved by implementing accounting accountability. At PT. SUR, the author has not seen the application of accounting accountability. Therefore, the author tries to discuss and interpret the data in the production section by comparing the realization of financing and budget deviations that are known to have occurred. Through accountability reports from the Outfitting Department, Construction Department and Production Support, management can measure the effectiveness and efficiency of production costs in the company. Thus, the company will not have difficulty in determining which costs from the many costs will affect decision making and improve the company's overall performance.) Keywords: Accountability Accounting, Implementation, Reporting, Management Accounting, Comparative Descriptiv